The effect of computer game on students' grammar acquisition-a focus on homonym, synonym and antonym / Muhammad Aiman Abdul Halim - Abdul Halim, Muhammad Aiman (Faculty of Education, 2014)
In the past few years, numerous researches had been conducted on educational computer games. However, there is no clear evidence on whether educational computer game is applicable in Malaysian classroom. This research will explore on the effectiveness of educational computer games on students’ performance in English grammar, specifically in the mastery of homonym, synonym and antonym. A total of 13 students from an urban secondary school had participated in this study, divided into two groups: treatment and control group. The educational computer game was developed by the researcher based on several software developmental models. The effectiveness of the computer game was tested through a pre-test and post-test, while students' level of motivation was measured using a questionnaire adapted from Keller's ARCS model of motivational design. This research found that the use of educational computer game in the classroom did not significantly improve students' performance and motivation.